Set of Elements, parameters and considerations to get the successful inclusion of the smart grids in colombian power systems (2015)
This document is a synthesis of those parameters, considerations, elements and systems that must be implemented if the objective is based on the inclusion of smart grids in the Colombian electrical system. This paper defines the changes of the traditional figure of the electrical energetic chains that includes generators, transmission, distributors, retailers and users to introduce the new concept of ProUser. This new term generates a change in the electrical chain and it will be become bidirectional and decentralized in operation.